Trustworthiness as a Source of Competitive Advantage - Barney, Jay B.; Hansen, Mark (Strategic Management Journal, 1994)
Three types of trust in economic exchanges are identified: weak form trust, semi-strong form trust, and strong form trust. It is shown that weak form trust can only be a source of competitive advantage when competitors invest in unnecessary and expensive governance mechanisms. Semi-strong form trust can be a source of competitive advantage when competitors have differential exchange governance skills and abilities, and when these skills and abilities are costly to imitate. The conditions under which strong form trust can be a source of competitive advantage are also identified. Implications of this analysis for theoretical and empirical work in strategic management are discussed.